(untitled) (Salam International Academic Journal, 2012)
In this part of the article, the author has sought to determine that vision, belief and values that make the foundation of the Western civilization. The beliet behind this civilization is totally atheistic belief which is summarized in the standpoint of this civilization regarding Allah (the summary of all the Western beliefs regarding Allah is such that according to these beliefs this world is totally free from the control and sovereignty of Allah: Allah has nothing to do with it, this world shall be managed according to the wishes of human mentality), the matter (the nature and the universe are not in need, neither in its coming into being nor in in its sustainability, to any supernatural being. The cosmos has come into being spontaneously and manages itself in accordance with the laws of nature), and the human (the human according to some Western philosophies shall either substitute Allah thereby invalidating the belief of theism and the Divine power or shall fully become part of the matter and nature without enjoying any difference with other natural things. There is no purpose behind the existence of human being. All laws applicable to other elements of nature shall also be applicable to human being. The human being has not come into being to worship anyone as is required by the Divine religions). The author has tried afterwards to determine a number of those characteristics appeared in the Western society as a result of the mentioned vision and belief at the end, the author has discussed the way of how to deal with this civilization.